Practical Interaction of Corporate Center and Divisions of National Companies in Russia - A. A. Kulikov (Вестник Российского экономического университета имени Г. В. Плеханова)
In situation of unprecedented economic sanctions, complete withdrawal of foreign companies from Russian market or cutting their effective product range, daily presidential and governmental acts aimed at population and business support, as well as potential new wave of COVID-19 the world forms new logistic links, brand new global structure and pays intent attention to potential and possibilities of Russia. By approaches to forms of interaction of corporate center and divisions discussed in works by G. Minzberg, D. Jonson, K. Showls, R. Wittington et al., as well as materials of the consulting companies McKinsey and KPMG, international standards of AA1000 series and analysis of the interview with spokespeople of divisions and corporate center the article identifies certain fields for the development of their interaction. They are formulated in the following way: to improve the system of information exchange, to take into account territorial specific features of each division in strategic planning, to develop the competence level of divisional heads and to search for degree of impact on the part of corporate center on division functioning depending on the level of executives’ training.